Menanamkan Pendidikan Karakter Siswa Melalui Permainan Tradisional Sasak “Benteng” di SDN 1 Pringgasela - Hafani, Rizda; Hadi, Yul Alfian; Saputra, Ahmad Yudi (Transformasi : Jurnal Penelitian dan Pengembangan Pendidikan Non Formal Informal, 2026)
Abstract: This study aims to determine how to instill character education in SDN 1 Pringgasela through the "Benteng" game and to determine the extent of the positive impact of the Sasak Benteng game on students’ character. This study used a qualitative method with a descriptive research type. The location of this research was SDN 1 Pringgasela. The objects of this study were fourth-grade students and the subjects were fourth-grade teachers. Data collection techniques used in this study were observation, interviews, and documentation. While data analysis used in this study were data reduction, data presentation, and drawing conclusions. The results of this study indicate that character education in SDN 1 Pringgasela, especially in fourth-grade students, can be instilled through the traditional Sasak Benteng game. Instilling character education in the traditional Sasak Benteng game at SDN 1 Pringgasela, researchers found that students enjoyed the game and were very enthusiastic about playing it. After the researchers introduced it, the students were very interested. The character traits students learned from playing Benteng included honesty, cooperation, discipline, unity, solidarity, responsibility, morality, self-confidence, sportsmanship, and sportsmanship. The positive impact of the traditional Sasak Benteng game on students’ character is that this traditional Sasak Benteng game is very suitable for instilling character education in students. There are many positive impacts when playing Benteng, as students can develop their character. By playing Benteng, students also learn that traditional games have many benefits, and that Sasak Benteng can also improve attitudes. Abstrak: Penelitian ini bertujuan untuk mengetahui bagaimana menanamkan Pendidikan karakter di SDN 1 Pringgasela pada permainan benteng dan untuk mengetahui sejauh mana dampak positif dari permainan sasak benteng pada karakter siswa. Penelitian ini menggunakan metode kualitatif, dengan jenis penelitian deskriftif, tempat pelaksanaan penelitian di SDN 1 Pringgasela, objek penelitian ini siswa kelas IV dan subjek yaitu guru kelas IV. Teknik pengumpulan data yang digunakan yaitu observasi, wawancara, dan dokumentasi, sedangkan analisis data yang digunakan adalah reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian ini menunjukkan bahwa Pendidikan karakter di SDN 1 Pringgasela khususnya dikelas IV dapat ditanamkan melalui permainan tradisional sasak benteng. Peneliti menemukan bahwa siswa menyukai permainan tradisional sasak benteng dan juga sangat bersemangat dalam memainkan permainan benteng, adapun karakter yang didapatkan siswa dalam bermain benteng yaitu jujur, kerjasama, disiplin, persatuan, solidaritas, bertanggung jawab, moral, percaya diri, sportivitas, olahraga. Dampak positif permainan tradisional sasak benteng bahwa permainan tradisional sasak benteng ini sangat cocok digunakan untuk menanamkan pendidikan karakter pada siswa. Dengan bermain benteng siswa juga dapat mengetahui permainan tradisional itu mempunyai banyak manfaat untuk dimainkan, dan juga permainan sasak benteng ini juga dapat meningkatkan sikap menjadi lebih baik.